Mental health services during the first wave of the COVID-19 pandemic in Europe: Results from the EPA Ambassadors Survey and implications for clinical practice - Rojnic Kuzman, Martina; Vahip, Simavi; Fiorillo, Andrea; Beezhold, Julian; Pinto da Costa, Mariana; Skugarevsky, Oleg; Dom, Geert; Pajevic, Izet; Peles, Alma Mihaljevic; Mohr, Pavel; Kleinberg, Anne; Chkonia, Eka; et al. (European psychiatry, 2021)
BACKGROUND: The COVID-19 pandemic caused an unprecedented worldwide crisis affecting several sectors, including health, social care, economy and society at large. The World Health Organisation has emphasized that mental health care should be considered as one of the core sectors within the overall COVID-19 health response. By March 2020, recommendations for the organization of mental health services across Europe have been developed by several national and international mental health professional associations. METHODS: The European Psychiatric Association (EPA) surveyed a large European sample of psychiatrists, namely the "EPA Ambassadors", on their clinical experience of the impact of COVID-19 pandemic on the treatment of psychiatric patients during the month of April 2020 in order to: a) identify and report the views and experiences of European psychiatrists; and b) represent and share these results with mental health policy makers at European level. Based on the recommendations issued by national psychiatric associations and on the results of our survey, we identified important organisational aspects of mental health care during the peak of the first wave of the COVID-19. RESULTS: While most of the recommendations followed the same principles, significant differences between countries emerged in service delivery, mainly relating to referrals to outpatients and for inpatient admission, assessments and treatment for people with mental disorders. Compared to previous months, the mean number of patients treated by psychiatrists in outpatient settings halved in April 2020. In the same period, the number of mentally ill patients tested for, or developing, COVID-19 was low. In most of countries, traditional face-to-face visits were replaced by online remote consultations. CONCLUSIONS: Based on our findings we recommend: 1) to implement professional guidelines into practice and harmonize psychiatric clinical practice across Europe; 2) to monitor the treatment outcomes of patients with COVID-19 and pre-existing mental disorders; 3) to keep psychiatric services active by using all available options (for example telepsychiatry); 4) to increase communication and cooperation between different health care providers.
Keywords: Surveys and Questionnaires; pandemie; Humans; lidé středního věku; psychiatrie; mental health services; Female; dospělí; Pandemics; lidé; společnosti lékařské; Europe; průzkumy a dotazníky; duševní poruchy; Adult; COVID-19; ženské pohlaví; Male; Middle Aged; Mental Health Services; Mental Disorders; Psychiatry; služby péče o duševní zdraví; Societies, Medical; mužské pohlaví; Evropa